Life aspirations of young adults with Asperger’s syndom from families experiencing migration - Anna Gagat Matuła; Bożena Frączek (Edukacja Ustawiczna Dorosłych, 2018)
The article discusses the issue of educational, professional and family aspirations among young adults with Asperger syndrome. The research is focused on families, where one of parents migrates to enhance economic status of family. There are substantial additional costs in families with member affected with Asperger's syndrome. It brings great impact on the family’s financial situation and many families with such problem experience financial hardships. In addition, in many countries there are unsatisfactory institutional financial support for these families. The migration of one of parent brings additional income, which can fill the financial deficit. On the other hand migration of one of parents influences the emotional situation in family. This study contributes a more detailed understanding of how the migration of one of parents influences the educational, professional and family aspirations among young adults with Asperger syndrome.